2015
DOI: 10.1109/tvt.2014.2359581
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Full-Duplex Systems in a Multispectrum Environment

Abstract: Our investigation focuses on the performance of fullduplex systems where both nodes simultaneously exchange their signals using a single spectrum for two-way communication.To maximize the achievable sum rate for full-duplex systems in multi-spectrum environments, we address a new selection strategy that considers the channel state of both nodes. The achievable sum rate for a multi-spectral bi-directional full-duplex (M-BFD) system is obtained using the proposed selection strategy and compared with conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is noticeable that the sum-rate of cell-boundary users in full-duplex is enhanced as M increases, even more than those of sum-rate values in the half-duplex system. This goes against the findings of previous works [20], [30]. This is because user-user interference and SI can be mitigated because the total transmission power of the BS and the transmit power of each user decrease as the number of antennas at the BS increases, [18], [19].…”
Section: Simulation Resultsmentioning
confidence: 60%
“…It is noticeable that the sum-rate of cell-boundary users in full-duplex is enhanced as M increases, even more than those of sum-rate values in the half-duplex system. This goes against the findings of previous works [20], [30]. This is because user-user interference and SI can be mitigated because the total transmission power of the BS and the transmit power of each user decrease as the number of antennas at the BS increases, [18], [19].…”
Section: Simulation Resultsmentioning
confidence: 60%
“…The bi-directional topology consists of pair FD nodes which transmit and receive signals at the same time and frequency. It has been shown that the bidirectional topology networks have the potential to double the spectrum efficiency over that of HD networks [12], [13]. In FD relay networks, the end-to-end latency can be reduced as a relay node can receive data from a source node and transmit data to a destination node simultaneously within all the same frequency band [11], [14].…”
Section: A Related Literaturementioning
confidence: 99%